2020
DOI: 10.30919/es8d1127
|View full text |Cite
|
Sign up to set email alerts
|

The Revelation of Various Compounds Found in Nigella sativa L. (Black Cumin) and Their Possibility to Inhibit COVID-19 Infection Based on the Molecular Docking and Physical Properties

Abstract: As there is no specified drug available to fight COVID-19, it is essential to have a different strategy to fight this virus. In the present study, using molecular docking, we have identified possible protease inhibitors of COVID-19 by the molecules present in Nigella sativa L. (black cumin), which is a reputed healing herb extensively used for processing Ayurvedic and Unani remedies. Herein, we perform molecular docking and study of various physical properties/descriptors of four derivatives of thymoquinone fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…They showed that among all the compounds tested, including chloroquine, which was included as a positive control, DTQ yielded the highest binding affinity (-8.6 kcal/mol) to the receptor binding domain (RBD) of SARS-CoV-2 S protein, thereby identifying DTQ as a potential inhibitor of SARS-CoV-2 interaction with the ACE2 receptor on the host cells and hence, its entry. Consistent with the above findings, N. sativa -derived compounds, including DTQ, THQ, thymol, and TQ were shown to dock with high affinity to the RBD of SARS-CoV-2 protein ( Shaikh et al., 2020 ). The fact that many of N. sativa ’s main compounds demonstrated a higher/comparable binding affinity to RBD relative to chloroquine, ( Ahmad et al., 2020 ) which is widely known to block virus entry, including SARS-CoV-2 entry ( Savarino et al., 2003 ; Wang, M. et al., 2020 ), is promising and shows the potential anti-SARS-CoV-2 activity of these compounds.…”
Section: Viruses As Important Human Pathogenssupporting
confidence: 75%
“…They showed that among all the compounds tested, including chloroquine, which was included as a positive control, DTQ yielded the highest binding affinity (-8.6 kcal/mol) to the receptor binding domain (RBD) of SARS-CoV-2 S protein, thereby identifying DTQ as a potential inhibitor of SARS-CoV-2 interaction with the ACE2 receptor on the host cells and hence, its entry. Consistent with the above findings, N. sativa -derived compounds, including DTQ, THQ, thymol, and TQ were shown to dock with high affinity to the RBD of SARS-CoV-2 protein ( Shaikh et al., 2020 ). The fact that many of N. sativa ’s main compounds demonstrated a higher/comparable binding affinity to RBD relative to chloroquine, ( Ahmad et al., 2020 ) which is widely known to block virus entry, including SARS-CoV-2 entry ( Savarino et al., 2003 ; Wang, M. et al., 2020 ), is promising and shows the potential anti-SARS-CoV-2 activity of these compounds.…”
Section: Viruses As Important Human Pathogenssupporting
confidence: 75%
“…Similar to our docking analysis, various research groups have verified an optimal interaction between N. sativa compounds and SARS-CoV-2 receptors and have predicted N. sativa as a plausible inhibitor to disrupt viral-host interactions. Shaikh et al [48] have conducted a similar docking study using N. sativa phytoconstituents as ligands and receptor-binding site of SARS-CoV-2 (PDB ID: 2AJF). The study reported that dithymoquinone, thy-mohydroquinone, thymol, and thymoquinone from this medicinal plant might inhibit COVID-19 infection giving the same or better energy score compared to chloroquine [48].…”
Section: Discussionmentioning
confidence: 99%
“…122 Molecular docking studies have already shown that TQ could potentially inhibit COVID-19 by binding to the receptor-binding domain on the spike protein of SARS-CoV-2, which would hinder virus entry into the host cell. 123 Additionally, it may bind to the SARS-CoV-2 envelope protein and inhibit its ion channel and pore formation activity. 124 Other studies have shown that TQ might display inhibitory action against the SARS CoV2 protease, which would halt viral replication.…”
Section: Molecular Docking Studies Related To Anti-covid-19 Activitymentioning
confidence: 99%